(untitled) (JS (JURNAL SEKOLAH), 2021)
Abstract: The learning achievement of students in class V SDN Winong 01 is relatively low, especially when Distance Learning (PJJ) is being carried out as it is now. This study aims to find out how to increase learning achievement through a Problem Based Learning model assisted by audiovisual media for fifth grade students at SDN Winong 01 on theme 9. This research is a Classroom Action Research conducted in class V SDN Winong 01. In this study, it was carried out in 3 cycles with subject as many as 13 students. The results of the research that have been carried out show that learning achievement has increased every cycle. The increase in the percentage of students’ learning achievement scores before being given action is 38.46% complete the KKM and the average achievement is 61.92 then in the first cycle it increases by 53.84% complete the KKM with an average achievement of 67.38 , increased again in the second cycle as much as 76.92% completed KKM with an average achievement obtained of 76.53 and increased again in the third cycle with KKM completeness of 92.31% with an average achievement obtained of 83.46. The conclusion of the learning outcomes shows that learning theme 9 through the Problem Based Learning learning model assisted by audio-visual media can improve the learning achievement of the fifth grade students of SDN Winong 01. Keywords: Learning Achievement, PBL, Audiovisual Media Abstrak: Prestasi belajar peserta didik di kelas V SDN Winong 01 tergolong rendah, terutama saat Pembelajaran Jarak Jauh (PJJ) yang dilaksanakan seperti sekarang ini. Penelitian ini bertujuan untuk mengetahui bagaimana peningkatan prestasi belajar melalui model Problem Based Learning berbantu media audiovisual peserta didik kelas V SDN Winong 01 pada tema 9. Penelitian ini merupakan Penelitian Tindakan Kelas yang dilakukan di kelas V SDN Winong 01. Dalam penelitian ini dilaksanakan sebanyak 3 siklus dengan subjek sebanyak 13 peserta didik. Hasil penelitian yang telah dilaksanakan menunjukkan bahwa prestasi belajar mengalami peningkatan setiap siklusnya. Peningkatan presentase nilai prestasi belajar peserta didik sebelum diberikan tindakan yaitu sebanyak 38,46% tuntas KKM dan capaian rata-rata diperoleh 41,86 kemudian pada siklus I meningkat sebanyak 53,84% tuntas KKM dengan capaian rata-rata yang diperoleh sebesar 67,38, meningkat kembali pada siklus II sebanyak 76,92% tuntas KKM dengan capaian rata-rata yang diperoleh sebesar 76,53 dan meningkat kembali pada siklus III dengan ketuntasan KKM sebesar 92,31% dengan capaian rata-rata yang diperoleh sebesar 83,46. Simpulan hasil pembelajaran menunjukkan bahwa pembelajaran tema 9 melalui model pembelajaran Problem Based Learning berbantu media audiovisual dapat meningkatkan prestasi belajar peserta didik kelas V SDN Winong 01. Kata Kunci : Prestasi Belajar, PBL, Media audiovisual